The relationship between esophageal acid exposure and the esophageal response to volumetric distention. Issue 3 (2nd November 2017) - Carlson, D. A.; Kathpalia, P.; Craft, J.; Tye, M.; Lin, Z.; Kahrilas, P. J.; Pandolfino, J. E.
Abstract: Background: Increased esophagogastric junction (EGJ) distensibility is thought to contribute to gastroesophageal reflux disease (GERD). Using the functional lumen imaging probe (FLIP), we aimed to assess the esophageal response to distension among patients undergoing esophageal pH monitoring. Methods: 25 patients (ages 22‐73; 13 females) who underwent ambulatory wireless esophageal pH testing while off proton‐pump inhibitors were evaluated with FLIP during sedated upper endoscopy. Esophageal reflux was quantified by total percent acid exposure time (AET; <6% was considered normal). FLIP studies were analyzed using a customized program generate FLIP topography plots to identify esophageal contractility patterns and to calculate the EGJ‐distensibility index (DI). Reflux symptoms were assessed with the GERDQ. Values reflect median (interquartile range). Results: Among all patients, the AET was 7.2% (3.7‐11.1) and EGJ‐DI was 4.2 (2.5‐7.6) mm 2 /mm Hg. Repetitive antegrade contractions (RACs) were induced in 19/25 (76%) of patients; AET was lower among patients with (6.1%, 3‐7.8) than without (14.9, 8.5‐22.3) RACs ( P = .009). Correlation was weak and insignificant between AET and EGJ‐DI, GERDQ and AET, and GERDQ and EGJ‐DI. Patients with abnormal AET (n = 16) and normal AET (n = 9) had similar EGJ‐DI, 4.6 mm 2 /mm Hg (2.9‐9.2) vs 3.2 (2.2‐5.1), P = .207 and GERDQ, P = .138. Conclusions: Abnormal esophageal acid exposure was associated with an impaired contractile response to volume distention of the esophagus. This supports that acid exposure is dependent on acid clearance mechanisms. Abstract : Among patients evaluated for reflux with wireless esophageal pH testing and the functional lumen imaging probe, a response to volumetric distension comprising repetitive, antegrade contractions (as in A) was associated with a reduced degree of esophageal acid exposure. The esophagogastric‐junction distensibility index, however, was poorly correlated with esophageal acid exposure.